Primary care dental professionals' experiences of sharp injuries in Qatar: A cross-sectional study - Marji, Tamara; Syed, Mohamed Ahmed (Frontiers in Oral Health, 2022)
Objectives Very few studies assess sharp injuries solely among dental professionals globally. This study aims to understand the experiences of sharp injuries among primary care dental professionals in Qatar. Methods This is a cross-sectional study where dental professionals working at the Primary Health Care Corporation (PHCC), a public sector healthcare organization and Qatar's largest primary care provider with 27 primary healthcare centers in Qatar, were invited to participate. An online questionnaire was administered to understand participants' experience of sharp injuries and access to occupational health services and training. Findings A total of 114 dental professionals participated in this study. In total, 68.42% (N=78) of participants reported experiencing a sharp injury in the 12 months prior to the survey. Majority (N=58; 75.36%) of the reported causes of sharp injuries were related to dental explorers (N=31; 40.26%) and dental injection needles (N=27; 40.26%). Of those who had experienced a sharp injury, 84.47% (N=87) did not report them. Conclusion In conclusion, the results highlight that sharp injuries are common among primary care dental professionals, and despite having good access to occupational support services, most dental professionals did not report their injuries. Continuous education and training programs must be implemented to improve knowledge and raise awareness to reduce the burden of sharp injuries among dental professionals. More studies from other dental settings are needed to better understand dental professionals' experiences of sharp injuries in Qatar and elsewhere.